Strategi Visual Branding dan Desain Kemasan Produk Pupuk Organik Cair (POC) Berbasis Limbah Dapur di Desa Lubuk Banjar - Jannah, Rizkia Zahratul; Loka, David Chandra; Ananda, Wahyu Rizky; Asmawita, Pipin; Mardalena, Erfin (Indo-MathEdu Intellectuals Journal, 2026)
The processing of household kitchen waste into liquid organic fertilizer (POC) is a sustainable effort that has the potential to reduce environmental pollution while increasing the economic value of rural communities. However, POC products produced at the village level generally still face limitations in terms of visual branding and packaging design, making them less competitive in the market. This activity aims to describe the process of assisting the community in developing visual branding and packaging design for kitchen waste-based POC products in Lubuk Banjar Village. The method used is a participatory descriptive approach through the stages of needs analysis, brand identity planning, and visual design assistance. Data was obtained through observation, discussions with the community, and documentation during the assistance process. The results of this activity show that consistent visual identity design, including logos, packaging stickers, and product messages, can increase visual appeal and clarify product information. Design assistance also improves the community's understanding and skills in managing product appearance independently. In addition, the use of digital media as a means of promotion provides opportunities to expand the marketing reach of POC products. This activity demonstrates that strengthening visual branding through participatory assistance plays an important role in increasing the added value and competitiveness of POC products based on local potential